God willing? : political fundamentalism in the White House, the "War on Terror," and the echoing press - Domke, David Scott (Pluto Press, 2004)
In the aftermath of the September 11 terrorist attacks, President George W. Bush and his administration offered a 'political fundamentalism' that capitalized upon the fear felt by many Americans. Political fundamentalism is the adaptation of a conservative religious worldview, via strategic language choices and communication approaches, into a policy agenda that feels political rather than religious. These communications dominated public discourse and public opinion for months on end and came at a significant cost for democracy.